Implikasi Ketiadaan Mata Pelajaran Kaligrafi Arab Terhadap Kemampuan Menulis Bahasa Arab Siswa di Sekolah Mengenah Atas (SMA) Negeri 2 Percut Sei Tuan Deli Serdang Sumatera Utara - Ismi Nujaima (Yayasan Haiah Nusratul Islam, 2024)
Calligraphy is an art that can convey information to people who see it, both in terms of information from the past and information from Allah SWT because calligraphy is also found in the verses of the Koran. Calligraphy is also Arabic writing which has special rules for making letters, connecting letters, and also composing words and sentences and this is also a work of hand art that has its own beauty value. The method that the author used in this research was literature study and interviews with several informants or respondents who were several people from class XI at SMA Negeri 2 Percut Sei Tuan. Literature study was carried out by taking references from several books, journals, theses and several other references. The importance of calligraphy in the context of Arabic language education, both as a means of developing Islamic art, strengthening cultural identity, and beautiful writing skills. Based on the results of the author's research, it shows that Arabic calligraphy does not exist at SMA Negeri 2 Percut Sei Tuan, therefore some students' Arabic writing is still not good. However, for some students, their writing is already good because they are self-taught. That is why calligraphy lessons are both important and not according to some students